Adición de cannabis (Cannabis sativa) como promotor de crecimiento en el alimento de cerdos de cruce comercial en la etapa de crecimiento y acabado - Mera Contreras, Erika Sinaí (2024)
This research work was carried out in 10 experimental units, which was carried out in the sheds of the Faculty of Agricultural Sciences of the Technical University of Babahoyo, based on the addition of pulverized Cannabis in the previously formulated feed, with the aim of analyzing its effect as a growth promoter in commercial crossbreeding pigs in their phase II and III which corresponds to growth and finishing. For this research the methodology used was a completely randomized design, with a total of five treatments, including treatment zero being this the control treatment, remaining as follows, T0: Formulated balanced, T1: 2gr of Cannabis / Kg of feed, T2: 4gr of Cannabis / Kg of feed, T3: 6gr of Cannabis / Kg of feed and a T4: 8gr of Cannabis / Kg of feed and two repetitions. The analysis of the data collected in each of the variables evaluated was carried out using the Tukey statistical test at 5%, the results obtained were positive determining that treatment 3 was the most significant with results of 66.52 kg in its live weight gain, a feed conversion of 2.66 kg for 1 kg of live weight, regarding the variable feed consumption, T3 and T4 obtained a higher consumption with 200.9 kg in both, with respect to the cost benefit, the use of cannabis as an additive gave profitable results, concluding that cannabis or hemp offers benefits in pig production since it has high levels of protein, the cannabis used had a value of 22.52% protein, in addition it did not present negative alterations in the organoleptic properties of the meat.